(untitled) (Journal of Engineering, 2011)
A low speed open circuit wind tunnel has been designed, manufactured and constructed at the Mechanical Engineering Department at Baghdad University - College of Engineering. The work is one of the pioneer projects adapted by the R & D Office at the Iraqi MOHESR. The present paper describes the first part of the work; that is the design calculations, simulation and construction. It will be followed by a second part that describes testing and calibration of the tunnel. The proposed wind tunnel has a test section with cross sectional area of (0.7 x 0.7 m2) and length of (1.5 m). The maximum speed is about (70 m/s) with empty test section. The contraction ratio is (8.16). Three screens are used to minimize flow disturbances in the test section. The design philosophy is discussed and methods for wind tunnel calculation are outlined. Simulation of wind tunnel using ANSYS shows no separation of flow along wind tunnel. Construction steps are also included in present work.